DETERMINAN BREASTFEEDING SELF-EFFICACY MATERNAL DAN PATERNAL KEHAMILAN HINGGA ENAM BULAN POSTPARTUM: SYSTEMATIC LITERATURE REVIEW - Siti Rohani; Sri Achadi Nugraheni; Dwi Maryanti; Yogi Andhi Lestari; Yuni Sulistiawati (Institut Citra Internasional, 2026)
Breastfeeding Self-Efficacy (BSE) is a key psychological factor determining a mother's success in initiating, maintaining, and completing exclusive breastfeeding practices. Despite the increasing number of studies on maternal BSE, many mothers and fathers still face modifiable barriers in practice, resulting in decreased self-confidence and suboptimal exclusive breastfeeding coverage for six months. This systematic review aims to identify and synthesize individual, interpersonal, and healthcare system factors associated with increased or decreased maternal and paternal BSE from pregnancy to six months postpartum. The review process followed the PRISMA process, with research questions formulated using the PECO (Population, Exposure, Comparator, Outcome) framework. A literature search was conducted in Scopus, PubMed, and Science Direct databases using structured keywords. Included articles were original English-language studies, fully open access, and published between 2021 and 2025, with a step-by-step selection process based on established inclusion and exclusion criteria. The study results indicate that husband support and the quality of the husband-wife relationship are very strong determinants of BSE strengthening, both in mothers and fathers. Furthermore, system factors such as the quality of lactation counseling, the implementation of antenatal and postnatal classes, and interventions that explicitly involve fathers have also been shown to contribute to BSE improvement. These findings confirm that maternal and paternal BSE are modifiable constructs through strengthening individual resources, couple dynamics, and support from the health care system.